Review essay: Alternative histories of revolutionaries in modern South Asia: context, chronology, and archives. Issue 3 (27th May 2019) - Amstutz, Andrew
Abstract: This review essay discusses two recent monographs on revolutionaries and political violence in South Asia, Kama Maclean's A Revolutionary History of Interwar India: Violence, Image, Voice and Text (2015) and Durba Ghosh's Gentlemanly Terrorists: Political Violence and the Colonial State in India, 1919-1947 (2017). Ghosh and Maclean's books contribute to an expanding body of scholarly work on anticolonial politics in India, a rich historiography on liberalism in the British Empire, and studies of visual culture and oral histories in modern South Asia. Specifically, Maclean's A Revolutionary History centers on the Hindustan Socialist Republican Army (HSRA) in Punjab and Delhi in the late 1920s and early 1930s. Maclean reconfigures the political terrain of India's independence struggle and illustrates the importance of revolutionary violence in nonviolent politics through unstudied visual sources and oral histories. In turn, Ghosh's Gentlemanly Terrorists focuses on Bengal, particularly revolutionaries in the Anushilan Samiti and Jugantar from 1919 to 1947. Complicating the history of colonial constitutionalism as a gradual expansion of rights and representation, Ghosh demonstrates how constitutional reforms that aimed to promote liberal governance in India were tied to repressive emergency legislation. This review essay addresses how Gentlemanly Terrorists and A Revolutionary History contribute to ongoing efforts to rethink both the political chronology and the wider political landscape of interwar India by incorporating revolutionaries into the story of independence. It also considers how Maclean and Ghosh creatively utilize non-state archives and vernacular sources, in conjunction with colonial records, to follow the retelling of revolutionary histories in different media.